Analyzing D'Masiv "Jangan Menyerah" as a Foundation for Character Education and the Development of Music, Dance, and Theatre Teaching Materials in Senior High School - Faisal Faisal; Erna Setianingsih (Tamaddun Life, 2026)
Arts and Culture education in Indonesian senior high schools continues to face a persistent challenge: the integration of character values into learning experiences that are authentic, affective, and aligned with adolescents' aesthetic worlds. Many teaching materials remain repetitive across school levels and tend to emphasize technical and theoretical knowledge rather than students' lived experiences, emotional development, and moral formation. In response to this issue, this study examines D'Masiv's popular song "Jangan Menyerah" as a potential foundation for character education and for the conceptual development of integrated teaching materials in music, dance, and theatre. This research employed a descriptive qualitative design using document analysis. The primary data consisted of the song lyrics, official audio recording, and official music video, while the secondary data included Merdeka Curriculum documents, the Pancasila Student Profile, and relevant scholarly literature on character education, popular music, and arts pedagogy. Data were analyzed through repeated reading and viewing, meaning-unit coding, thematic categorization, and source triangulation across verbal, musical, and visual-narrative data. The findings identify six major character values embedded in the song: perseverance and independence, optimism and hope, religiosity and spirituality, emotional resilience, social concern and empathy, and responsibility and courage. These values are reinforced by the song's reflective minor tonality, moderate tempo, dynamic contrast, coherent popular-song structure, and expressive vocal texture. The study further demonstrates that these values correspond closely to the Pancasila Student Profile and to the developmental needs of senior high school students. The analysis is then translated into conceptual teaching-material designs for music appreciation and singing practice, dance movement exploration and creative choreography, theatre character analysis and scriptwriting/acting, and an integrated musical-theatre performance project. The study contributes theoretically to character-based arts education and practically to the development of contextual, project-based, and adolescent-relevant Arts and Culture learning materials.